Residential field site training project abstracts - 47th Batch Session: 2004-2005, 4th year MBBS students, CMC - Editor, The (Journal of Chittagong Medical College Teachers’ Association, 2010)
DOI: 10.3329/jcmcta.v20i2.5631 Journal of Chittagong Medical College Teachers' Association 2009: 20(2):60-63